A review of current energy systems and green energy potential in Kazakhstan - Karatayev, Marat; Clarke, Michèle L. (Elsevier, 2016)
Kazakhstan is rich in natural resources including coal, oil, natural gas and uranium and has significant renewable potential from wind, solar, hydro-power and biomass. In spite of this, the country is currently dependent upon fossil fuels for power generation. Coal fired plants account for 75% of total power generation leading to concerns over greenhouse gas emissions and impacts on human health and the environment. Recent economic growth in Kazakhstan has driven increased demand for energy services, making the construction of additional generating capacity necessary for enabling sustained economic growth. In this context, renewable energy resources are becoming an increasingly attractive option to help bridge the demand–supply gap and to decrease national greenhouse gas emissions. This study presents an overview of the existing energy system in Kazakhstan and investigates policy drivers for the energy sector. We review existing studies, national reports, energy strategies and plans, to identify and describe key barriers that prevent diffusion of renewable energy technologies in Kazakhstan. We propose potential measures to overcome specific barriers in order to successfully develop a renewable energy sector in Kazakhstan. It is seen that the likely major contributors to replacing fossil fuel based energy services are likely to be wind power and solar energy technologies, with biomass and hydro energy sources likely to play a lesser role. The barriers to development include low electricity tariffs, transmission losses and inefficient technologies, weak regulatory and legal frameworks and a high-risk business environment.